Analisis SWOT pada Produk KUR Syariah di PT. Pegadaian Syariah Kabupaten Pinrang - A. Nur Hazizah; Desy Arum Sunarta; Andi Bisyriani (STAI DDI Pinrang, 2025)
This study is entitled SWOT Analysis on Sharia KUR Products at PT. Pegadaian Syariah Pinrang Regency. The main objective of this study is to analyze SWOT on Sharia KUR products at PT. Pegadaian Syariah Pinrang Regency. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study indicate that 1) a financing mechanism based on sharia principles aimed at micro, small, and medium enterprises (MSMEs). The marketing strategy for this product is not too aggressive because it is widely known by customers as a product with low interest. However, there are several shortcomings, namely the absence of collateral in the loan, so that if there is arrears, the collection process becomes difficult. The main obstacle in submitting KUR is usually related to filing, such as incomplete business permits. 2) SWOT analysis is a strategic planning method used to evaluate Strengths, Weaknesses, Opportunities, and Threats in a business, project, or organization. The demand for KUR is quite high with many enthusiasts and submission of files